PENERAPAN MODEL KOOPERATIF TIPE TEAM GAMES TOURNAMENT UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA SMP - Ni'am, Fai'dun; Widodo, Wahono (Program Studi S1 Pendidikan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2023)
This study aimed to describe the learning outcomes of attitudes, knowledge, and skills with a Team Games Tournament (TGT) type cooperative learning model in science learning human excretory system material at one of the junior high schools in Gresik. The type of research is quantitative pre-experiment with one group pretest posttest design research design which was tested on 30 students. The instruments used are observation sheets (assessment of attitudes, and skills), and test sheets pretest-postest. The data obtained were then analyzed by score analysis and attitude and skill assessment criteria, and test analysis with Shapiro Wilk normality test, Wilcoxon hypothesis test, and N-Gain. The results showed that the application of the TGT cooperative learning model increased, in terms of the increase in pretest and posttest which obtained an average N-Gain of 0.77 in the high category. Attitude learning outcomes also improved from meetings I, II, and III with an average of 82.22 in the very good category. In addition, the students' skill learning outcomes obtained an average of 84.38 with very good criteria. Based on the results of the research, it was concluded that the application of the TGT cooperative learning model can improve student learning outcomes.